Sistem Informasi Jasa Repaint Vespa Pada Bengkel Cat Karya Mandiri - galuh arvana galuh; Tintin Harlina (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2023)
The aim of this research is to develop a web-based information system for repaint services at Karya Mandiri Paint Workshop. In constructing this system, the researcher employed the waterfall methodology, which consists of five phases: system requirements analysis, system design, implementation, system testing, and maintenance. This study resulted in a web-based application for the information system of repaint services at Karya Mandiri Paint Workshop. The system allows for customer data entry, order data input, addition of paint color data, and recording of repaint order queues. The built repaint service system can assist Karya Mandiri Paint Workshop and has been verified through blackbox testing to function effectively